Gender differences in access to health care among the elderly evidence from Southeast Asia. - van der Meulen Rodgers; Asian Development Bank (Manila,Philippines Asian Development Bank, [2021])
Using household survey data, the paper finds that while women in Cambodia and the Philippines are more likely to seek treatment than men, the gender difference is reversed in Viet Nam where stigma associated with some diseases may more strongly deter women than men. The probability of seeking treatment rises with age more sharply for women than men. Yet, for the subsample of elders, the gender difference is not significant.
Keywords: Gender -- Health and hygeine; Aging, elderly -- Health system development; Electronic book